2017
DOI: 10.1002/jcop.21920
|View full text |Cite
|
Sign up to set email alerts
|

Cultural stressors, identity development, and substance use attitudes among Hispanic immigrant adolescents

Abstract: The goal of this investigation was to determine whether various cultural stressors (bicultural stress, perceived discrimination, and per-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 67 publications
3
15
0
Order By: Relevance
“…Our findings suggest that youth who perceive their communities to be unwelcome or offer few opportunities to members of their ethnic group, experienced more symptoms of anxiety and depression than their peers who felt welcome and hopeful about their prospects. This aligns with studies that have assessed the association between negative PCOR and behaviors such as aggression, violence, and substance use (Forster et al, 2015; Schwartz et al, 2015) and key features of adolescence such as identity development (Grigsby et al, 2018). If perceptions that communities are unwelcoming persist or youth believe they have fewer opportunities for success, the stress associated with these beliefs can diminish the capacity of future functional coping (Bar‐On et al, 2003) and potentially increase vulnerablity for chronic stress conditions that challenge psychological and behavioral health in adulthood (McEwen, 2003).…”
Section: Discussionsupporting
confidence: 80%
“…Our findings suggest that youth who perceive their communities to be unwelcome or offer few opportunities to members of their ethnic group, experienced more symptoms of anxiety and depression than their peers who felt welcome and hopeful about their prospects. This aligns with studies that have assessed the association between negative PCOR and behaviors such as aggression, violence, and substance use (Forster et al, 2015; Schwartz et al, 2015) and key features of adolescence such as identity development (Grigsby et al, 2018). If perceptions that communities are unwelcoming persist or youth believe they have fewer opportunities for success, the stress associated with these beliefs can diminish the capacity of future functional coping (Bar‐On et al, 2003) and potentially increase vulnerablity for chronic stress conditions that challenge psychological and behavioral health in adulthood (McEwen, 2003).…”
Section: Discussionsupporting
confidence: 80%
“…An additional limitation that was not examined and has been shown to be important in previous literature is reception or the level of friendliness a community displays to an immigrant population (Forster, Grigsby, Soto, Schwartz, & Unger, 2015; Grigsby et al, 2018; Schwartz et al, 2014). As communities differ in openness toward immigrants, including language preferences and cultural practices, future investigation of receptions’ impact on acculturative stress and discrimination in Latinx immigrants would be critical to contribute to the literature (Forster et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Scholars have suggested that this sense of confusion or feeling lost may contribute to risky behaviors and attitudes (Schwartz et al, 2006). In fact, a longitudinal study with recently immigrated Latinx adolescents found that being poorly received by the host community can increase positive attitudes toward alcohol use (Grigsby et al, 2018). As such, the current findings supported the notion that social cohesion could serve a protective function even after controlling for family support, a commonly identified resource in Latinx research (Corona et al, 2017; Valdivieso-Mora et al, 2016).…”
Section: Discussionmentioning
confidence: 99%